2021
DOI: 10.15376/biores.17.1.207-222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical steeping on yields of glucose and xylose from dilute acid hydrolysis of extract from oil palm trunk

Abstract: The effectiveness of chemical steeping was examined as a novel pretreatment prior to hydrolysis to influence the extractable yield of glucose and xylose from oil palm trunk (OPT). The chemical steeping parameters were 0.2% sodium metabisulphite (w/v), 0.5% lactic acid (v/v), 26 ± 2 °C, and 1 h, followed by dilute acid hydrolysis (2%, 4%, and 6% of sulphuric acid (v/v); 115 °C, 120 °C, and 130 °C; 15 min, 30 min, and 60 min). For comparison, the glucose and xylose yield extracted from untreated OPT was also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ 35 ] In this case, fiber competes with starch for the limited amount of water, as occurred with amaranth flour and defatted coconut flour starch supplementation. [ 37 ] Reyes et al [ 38 ] studied the effect of starch oxidation at high temperature and observed effect on theology characteristics and carbonyl groups. This changes could be happened in residual starch present in pericarp and be affected during extrusion.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] In this case, fiber competes with starch for the limited amount of water, as occurred with amaranth flour and defatted coconut flour starch supplementation. [ 37 ] Reyes et al [ 38 ] studied the effect of starch oxidation at high temperature and observed effect on theology characteristics and carbonyl groups. This changes could be happened in residual starch present in pericarp and be affected during extrusion.…”
Section: Resultsmentioning
confidence: 99%
“…OPT contains fibrous materials which can be used in many industries, such as plywood, laminated veneer lumber, woodcement composites, gypsum board, pulp and paper making, animal feeds, and other value-added products [14,15]. The squeezed sap from old OPT contained mainly glucose, fructose, sucrose, and small amounts of galactose, xylose, and rhamnose, whose total amounts varied between 16.97-140 g/L [16][17][18]. Additionally, oil palm sap contains minerals, vitamins, organic acids, and amino acids [15,19].…”
Section: Introductionmentioning
confidence: 99%